2014
DOI: 10.1115/1.4027904
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Turbines for Mini-Organic Rankine Cycle Power Systems

Abstract: Organic Rankine cycle (ORC) power systems are rapidly diffusing as a technology for the conversion of thermal energy sources in the small-to-medium power range, e.g., from 150 kWe up to several MWe. The most critical component is arguably the expander, especially if the power capacity is small or very small, as it is the case for innovative high-potential applications such as waste heat recovery from truck engines, or distributed conversion of concentrated solar radiation. In these so-called high-temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 14 publications
0
42
0
1
Order By: Relevance
“…Consequently, and in order to enhance the robustness of the optimization, a gradientfree optimizer is commonly adopted, see, e.g., Refs. [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, and in order to enhance the robustness of the optimization, a gradientfree optimizer is commonly adopted, see, e.g., Refs. [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the ORC field, Fiaschi et al [6] have suggested the use of radial inflow turbines as advantageous solutions in the small power range due to their compact structure, higher enthalpy drop per stage and insensitivity to load variation at off-design. In the context of radial turboexpanders, novel architectures have been studied by Persico et al [7], Pini et al [8] and Casati et al [9], who have highlighted the specific flow features and advantages of centrifugal turbine configurations for high-temperature and small-power output applications. Axial turbines are generally adopted for high mass flow rates and in multistage configurations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…High temperature heat sources such as exhaust gases from internal combustion engines require very high pressure ratios, which are achieved by a turbo-expander such as those presented in [5,6]. The relatively small enthalpy drop of organic fluids permits these pressure ratios to be achieved over a single stage, but at the expense of introducing supersonic flows within turbine.…”
Section: Introductionmentioning
confidence: 99%